The Influence of Financial Literacy and Income on Investment Decisions Mediated by Financial Behavior in Msmes in Buleleng - Ni Luh Eka Ayu Permoni; Anak Agung Ayu Restitiati; Mertyani Sari Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study reveals that financial literacy and income positively and significantly influence investment decisions and financial behavior among MSME owners in Buleleng. Better financial literacy enhances both financial behavior and investment decisions, while higher income improves financial behavior and leads to increased investment decisions. Additionally, financial behavior serves as a mediating factor, amplifying the positive effects of financial literacy and income on investment decisions. This indicates that a combination of strong financial literacy, higher income, and good financial behavior contributes significantly to better investment decision-making among business owners.